(untitled) (Altre Modernità, 2018)
The following article focuses on the American Anthology by Dany Laferrière, a writer originally from Haiti who decided, following his voluntary exile in Québec, to publish exclusively in Montreal and in French and to live in Miami. "Auteur déplacé", he does not like classifications: black, Haitian, French, Quebec, etc., but is considered an American writer tout court. His Americanness, accompanied by an opaque, nomadic and wandering writing style, reveals a plural identity belonging and a hybrid cultural belonging. Montréal, Miami, New York are just his writing spaces, because for Laferrière literature is a journey and not a place of confinement. L’article suivant est axé sur l’Anthologie américaine de Dany Laferrière, écrivain originaire de Haïti qui a néanmoins décidé, à la suite de son exil volontaire au Québec, de publier exclusivement à Montréal et en français et de vivre à Miami. “Auteur déplacé”, il n’aime pas les classifications (noir, haïtien, francophone, québécois, etc.), mais il se considère comme un écrivain américain tout court. Son américanité, accompagnée d’une écriture opaque, nomade et errante, révèle une appartenance identitaire plurielle et une appartenance culturelle hybride. Montréal, Miami, New York ne sont que ses espaces d’écriture car, pour Laferrière, la littérature est un voyage et non pas une frontière.